2021
DOI: 10.46303/ressat.2021.40
|View full text |Cite
|
Sign up to set email alerts
|

E-learning Facilities for Teaching Secondary School Physics: Awareness, Availability and Utilization

Abstract: Secondary school physics contribute significantly to the technological development of a nation because it lays the foundation for further studies in physics. Physics is an abstract science subject that relies greatly on practical, and the crucial role played by the use of instructional materials especially, e-learning facilities in this 21st century cannot be over emphasized. This study investigates the awareness, availability and utilization of e-learning facilities among secondary school physics teachers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…This result agrees with John (2019) who found out that poor infrastructures and material resources exist in secondary school thus posing a hinderance to the effective teaching of physical science (chemistry and physics). The finding from the study also agrees with Akinbobola and Bada (2019) and Bada and Jita (2021) who found out that inadequate facilities such as laboratory and e-learning facilities were not readily available for use during the teaching of secondary school physics respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This result agrees with John (2019) who found out that poor infrastructures and material resources exist in secondary school thus posing a hinderance to the effective teaching of physical science (chemistry and physics). The finding from the study also agrees with Akinbobola and Bada (2019) and Bada and Jita (2021) who found out that inadequate facilities such as laboratory and e-learning facilities were not readily available for use during the teaching of secondary school physics respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Setlhako (2018) noted that initial teacher training programs should be tailored to target the abilities and proficiencies needed by teachers in the 21st century and prepare them for 4IR to meet the requirements and demands of future generations. The curriculum should link formal education to the outside-of-the-classroom working environment (Bada & Jita, 2021;Setlhako, 2018). Thus, there is a need for posthuman pedagogy, which Yan et al (2020) describe as having four characteristics: posthuman pedagogy in terms of learner, instructional material, technology (nonhuman actors), and ethical behavior.…”
Section: Role Of Science Education Toward Social Changementioning
confidence: 99%
“…Akan tetapi Loosemore et al (2021) mengatakan inisiatif pengadaan dan manajemen bagi fasilitas pendidikan sangat penting. Beberapa Negara berkembang lain bahkan dalam hal ini telah mencanangkan program pengadaan pangan bagi sekolah (Williams, 2021), walaupun pada sisi lain, memang persoalan mendasar dalam hal ini seperti temuan Yates et al (2019) selalu bermasalah pada soal pendanaan; juga ketersediaan dan pemanfatan yang secara khusus menurut Bada & Jita (2021) adalah praktik penggunaan bahan ajar. Dalam perspektif Nowicki (2021) cenderung menjadi tantangan daripada kemudahan.…”
unclassified